Phosphine-Catalyzed Asymmetric Allylic Alkylation of Isoxazol-5(4H)-ones with Morita-Baylis-Hillman Carbonates - Lei, Yuncong; Chen, Xuling; Jiang, Yantong; Li, Pengfei (Current Organocatalysis, 2025)
AimsPhosphine-catalyzed asymmetric allylic alkylation of isoxazol-5(4H)-ones with achiral Morita-Baylis-Hillman (MBH) carbonates has been developed. A series of isoxazol-5(4H)-ones bearing all-carbon quaternary stereocenters were obtained in 55-96% yield with 75-90% ee. Gram-scale reaction and further transformation of allylation products were conducted to demonstrate the synthetic practicability.MethodsUnder Ar atmosphere, the mixture of isoxazol-5-one 1 (0.1 mmol), MBH carbonate 2 (0.12 mmol, 1.2 equiv), catalyst P5 (10 mol%), and 4Å MS (10 mg) in toluene (1 mL) was stirred at 0°C for 24 h. The solvent was removed under vacuum, and the residue was purified by flash chromatography (petroleum ether/ethyl acetate = 3/1) to provide product 3.Result and ConclusionWe developed an efficient and enantioselective allylic alkylation of isoxazol-5(4H)-ones with achiral MBH carbonates in the presence of chiral phosphine catalyst. A broad range of isoxazol-5(4H)-ones bearing all-carbon quaternary stereocenters were prepared with high efficiency and enantioselectivity. Importantly, the organocatalytic δ-stereocontrol of MBH carbonates was achieved via the synthetic strategy.
Keywords: asymmetric organocatalysis